Guiding the Origins of readings in the interpretation of AL Baidhawy (Died 685 AH) in Surat Al-Beqara - Mohamed , Youssef; Dhyab , Arkan (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah, Lord of the Worlds, peace and blessings be upon the noblest messengers of Muhammad, on his family and companions. Either: Since science is honored by its subjects, the science of the Qur'anic readings is the most honorable of these sciences; for their direct attachment to the Book of Allah One of the most important sciences, embraced in the science of readings is the science of guiding the readings. This science shows the faces of the Qur'anic readings in a word, and its agreement with the rules of language and grammar. It is a beautiful science, which deals with several sciences. Sometimes it draggles. To the science of interpretation, and deals with the stranger, and pamper and cite it with Quranic verse, and in the poems of the Arabs. Sometimes it shows the parsing face, So I called my research (guiding the origins of readings in the interpretation of AL Baidhawy[(Died 685 AH)]in Surat Al-Beqara). The research included an introduction and two researches. I have defined the guidance of the readings linguistically and idiomatically, the benefit of the diversity of readings, then direct the readings in a section to prod the single, and guide reading in the section of diphtheria, and directed it in the section endowment on the decree of the line .